2021
DOI: 10.1002/jmrs.537
|View full text |Cite
|
Sign up to set email alerts
|

Using the theory of planned behaviour to determine radiation protection among South African diagnostic radiographers: a cross‐sectional survey

Abstract: Introduction The use of ionising radiation in medicine accounts for the majority of radiation exposure from artificial sources. Therefore, all measures to safeguard against unnecessary radiation exposure must be taken. As radiographers are central to radiation protection, this study aimed to determine South African radiographers’ attitude towards radiation protection, subjective norm and perceived behavioural control concerning radiation protection. Methods This quantitative cross‐sectional study used an onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Within medical imaging, the TPB has been used to explain variation in the number of intra-oral radiographs acquired in different settings, 11 understand physicians’ use of contrast-enhanced ultrasound imaging, 12 explain variation in imaging referral patterns 12 and explore radiation protection practices. 13 The TPB is therefore an appropriate model to explain actions and behaviours in response to patient safety concerns in ultrasound practice.…”
Section: Methodsmentioning
confidence: 99%
“…Within medical imaging, the TPB has been used to explain variation in the number of intra-oral radiographs acquired in different settings, 11 understand physicians’ use of contrast-enhanced ultrasound imaging, 12 explain variation in imaging referral patterns 12 and explore radiation protection practices. 13 The TPB is therefore an appropriate model to explain actions and behaviours in response to patient safety concerns in ultrasound practice.…”
Section: Methodsmentioning
confidence: 99%
“…However, the first two phases of an explanatory, sequential, mixed-method study reported sub-optimal radiation protection in South Africa, prompting further inquiry [3 , 4] . The study's first quantitative phase [3] found that radiographers showed high intention towards radiation protection, but participants in the second qualitative phase [4] obser ved var ying radiation protection compliance in practice. The deterrents to optimal radiation protection included feeling rushed to complete exams, trauma patients and challenging patients, patients' knowledge of the effect of ionising radiation, imaging referrals, inadequate training and lack of resources and managerial support.…”
Section: Introductionmentioning
confidence: 97%
“…5,6 This article forms part of an explanatory, sequential, mixedmethod study 7 that previously added to the existing evidence base. 8 The first quantitative phase used the theory of planned behaviour to explore South African radiographers' radiation protection behaviour. The findings revealed that even though a few respondents use radiation protection, most respondents plan and intend to use radiation protection measures.…”
Section: Introductionmentioning
confidence: 99%
“…The second phase of the study explored the reasons for these results obtained in the first phase of the study. 8…”
Section: Introductionmentioning
confidence: 99%